1996
DOI: 10.1103/physrevb.54.12798
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical transition in sliding charge-density waves with quenched disorder

Abstract: We have studied numerically the dynamics of sliding charge-density waves (CDWs) in the presence of impurities in d=1,2. The model considered exhibits a first order dynamical transition at a critical driving force Fc between "rough" (disorder dominated) (F < Fc) and "flat" (F > Fc) sliding phases where disorder is washed out by the external drive. The effective model for the sliding CDWs in the presence of impurities can be mapped onto that of a magnetic flux line pinned by columnar defects and tilted by an app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 14 publications
10
49
1
Order By: Relevance
“…Although the above jump appears to indicate a firstorder transition, [14] we shall argue in Sec. VIII that the bulk magnetization in fact grows continuously at the transition when interactions are taken into account.…”
Section: A Exact Solution: a Point Impuritymentioning
confidence: 99%
See 2 more Smart Citations
“…Although the above jump appears to indicate a firstorder transition, [14] we shall argue in Sec. VIII that the bulk magnetization in fact grows continuously at the transition when interactions are taken into account.…”
Section: A Exact Solution: a Point Impuritymentioning
confidence: 99%
“…Thus we predict that a continuous phase transition is possible, in contrast to arguments based on depinning of a single line, which suggest a first-order transition. [14] A phenomenon like Bose condensation describes the physics of the tilted fraction of the lines, consistent with many lines entering just a few extended states above the mobility edge. However, because phase fluctuations are so strong in 1 + 1 dimensions, correlations of the boson parameter decay algebraically to zero at large distances instead of approaching a nonzero constant.…”
Section: Effect Of Interactions In Thementioning
confidence: 99%
See 1 more Smart Citation
“…The properties of the driven coherent phase were examined and discussed in [12][13][14][15][16]. Yet a number of unresolved problems remains.…”
mentioning
confidence: 99%
“…In fact, recent studies in one dimension [24-261 showed that, even when the product of the two eigenfunctions is delocalized, each of the eigenfunction shows a behavior intermediate between localized and delocalized. It is also suggested [3,15] that the eigenfunction in two dimensions is a fract.al object in the delocalized regime.…”
Section: Localization Length Of the Hermitian Anderson Modelmentioning
confidence: 99%